A study of five parallel approaches to a genetic algorithm for the traveling salesman problem - Eldridge, B. D., author; Roychowdhury, V. P., author; Siegel, H. J., author; Maciejewski, Anthony A., author; Wang, L., author; TSI® Press, publisher (Colorado State University. Libraries, 2005)
This paper presents a comparative study of five different coarse-grained parallel genetic algorithms (PGAs) using the traveling salesman problem as the case application. All of these PGAs are based on the same baseline serial genetic algorithm, implemented on the same parallel machine (IBM SP2), tested on the same problem instances, and started from the same set of initial populations. Based on these experiments, a PGA that combines a new subtour technique with a known migration approach is identified to be the best for the traveling salesman problem among the five PGAs being compared.
Keywords: parallel genetic algorithms; traveling salesman problem; memetic algorithms